Mutually Orthogonal Complementary Golay Coded Sequences: An In-vivo Study - TROTS, Ihor; TASINKIEWICZ, Jurij; NOWICKI, Andrzej (Archives of Acoustics, 2024)
Fast and high-quality ultrasound imaging allows to increase the effectiveness of detecting tissue changes at the initial stage of disease. The aim of the study was to assess the quality of ultrasound imaging using mutually orthogonal, complementary Golay coded sequences (MOCGCS). Two 16-bits MOCGCS sets were implemented in the Verasonics Vantage™ scanner. Echoes from a perfect reflector, a custom-made nylon wire phantom, a tissue-mimicking phantom, and in-vivo scans of abdominal aorta and common carotid artery were recorded. Three parameters of the detected MOCGCS echoes: signal-to-noise ratio (SNR), side-lobe level (SLL), and axial resolution were evaluated and compared to the same parameters of the echoes recorded using standard complementary Golay sequences (CGS) and a short, one sine cycle pulse. The results revealed that MOCGCS transmission maintained comparable echo quality metrics (SNR, SLL, and axial resolution) compared to CGS and short pulses. Notably, both MOCGCS and CGS offered similar SNR improvements (5 dB–9 dB) in comparison to the short pulse for wires placed at depths up to 8 cm. Analysis of axial resolution, estimated at the full width at half maximum level, revealed near-identical values for all transmitted signals (0.17 μs for MOCGCS, 0.16 μs for CGS, and 0.18 μs for short pulse). MOCGCS implementation in ultrasound imaging offers the potential to significantly reduce image reconstruction time while maintaining image quality comparable to CGS sequences. In the experimental study we have shown that MOCGCS offers advantages over conventional CGS by enabling two times faster data acquisition and image reconstruction without compromising image quality.